Microhardness Properties of Mineral Trioxide Aggregate and Calcium-enriched Mixture Cement Plugs at Different Setting Conditions - Tabrizizadeh, Mehdi (J Int Oral Health, 2015)
BACKGROUND: Providing an apical stop in open apex roots is one of the endodontic challenges. The aim of present study was to compare the surface hardness of both mineral trioxide aggregate (MTA) and calcium-enriched mixture (CEM) cement at different setting situations. MATERIALS AND METHODS: A total of 40 freshly extracted human teeth with a single root and normal apex and no obvious caries or curvatures were selected. The teeth were sectioned horizontally from the cement enamel junction and 2 mm above the apex. Standard technique was administered for cleaning and shaping of the canals. Open apex root canal was prepared by using Peso reamer. The prepared teeth were randomly divided into four groups in which two groups were filled by MTA and the other groups were filled by CEM. White MTA and CEM cement plugs were prepared and condensed up to the apical end. In two groups, moistened paper point was placed in the canals and in the other group dried paper points was used. Vickers test was done to evaluate the microhardness and the collected data were analyzed by Kruskal-Wallis and three-way ANOVA tests using SPSS software version 18 at a significant level of 0.05. RESULTS: The highest and lowest surface hardness was observed in CEM group at dried condition with 4 mm thickness indentation (145.10 ± 7.60 kg/mm(2)) and moist MTA group indented at 8 mm thickness (111.25 ± 5.37 kg/mm(2)). However, no significant difference was noticed (P > 0.05). CONCLUSION: Humidity condition might not influence the microhardness properties of both MTA and CEM cement apical plugs at different tested indentation thickness.